Effects of attention deficits on the auditory processing performance among normal and APD children - Sulaiman, Nur Hafizah; Dzulkarnain, Ahmad Aidil Arafat; Maamor, Nashrah; Rahmat, Sarah (2021)
Introduction: In a recent decade, the experts and audiology professional bodies across the world started to consider the involvement of top-down processing of higher-order cognitive functions, particularly attention, as a part of Auditory Processing Disorder (APD). Therefore, this study aimed to investigate the extension of the effect of attention on auditory processing performance among normal and APD children, particularly in the event that attention deficits also identified together with APD.